2008
DOI: 10.1080/03079450701802222
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of swollen sinuses in broilers by experimental infection with avian metapneumovirus subtypes A and B of turkey origin and their comparative pathogenesis

Abstract: Swollen head syndrome (SHS) associated with avian metapneumovirus (aMPV) subtype A or subtype B in broilers and broiler breeders has been reported worldwide. Data about pathogenesis of aMPV subtypes A and B in broilers are scarce. It has been difficult to reproduce swollen sinuses in chickens with aMPV under experimental conditions. In the field, SHS in broilers is suspected to be induced by combined infections with different respiratory pathogens. The objectives of the present study were to compare the pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…As Fig. 9B and a previous report indicate (47), the lung, trachea, oropharynx, and spleen of chickens are permissive for aMPV/B infection. These results suggested that these specific tissues facilitated aMPV/B infection via TMPRSS12 cleavage of the F protein.…”
Section: Ampv/b Grows In Vitro Without the Addition Of Trypsinsupporting
confidence: 73%
“…As Fig. 9B and a previous report indicate (47), the lung, trachea, oropharynx, and spleen of chickens are permissive for aMPV/B infection. These results suggested that these specific tissues facilitated aMPV/B infection via TMPRSS12 cleavage of the F protein.…”
Section: Ampv/b Grows In Vitro Without the Addition Of Trypsinsupporting
confidence: 73%
“…These infections are mainly characterized by nasal discharge, tracheal and facial congestion, and swollen infraorbital sinuses. 1 In laying birds, infection results in egg drops and poor egg quality. 2 aMPV belongs to the genus Metapneumovirus within the subfamily Pneumovirinae of family Paramyxoviridae and has a nonsegmented, single-stranded, negative-sense RNA genome.…”
Section: Introductionmentioning
confidence: 99%
“…Avian metapneumovirus (aMPV) belongs to the genus Metapneumovirus in the subfamily Pneumovirinae of the family Paramyxoviridae 1 . aMPV causes acute rhinotracheitis in turkeys of all ages and swollen head syndrome in chickens, resulting in a major economic burden for poultry farmers 2 . Since aMPV was first detected in South Africa in 1978, aMPV has been reported in many countries 3 .…”
mentioning
confidence: 99%